2022
DOI: 10.1071/rd22204
|View full text |Cite
|
Sign up to set email alerts
|

Maternal metabolic health and fertility: we should not only care about but also for the oocyte!

Abstract: Reduced oocyte quality, mainly due to mitochondrial dysfunction, is a key cause of subfertility in patients with metabolic diseases such as obesity. Recent fundamental understanding of the underlying mechanisms highlights the importance of developing effective preconception care strategies not only to improve metabolic health, but also oocyte quality. Minimizing mitochondrial oxidative stress either in vivo or in vitro is a promising solution, however further investigations should consider the long-term conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 194 publications
0
8
0
Order By: Relevance
“…Oocyte development in a lipotoxic environment is thought to be one of the main negative effects of maternal obesity on fertility, as it promotes direct impairment of oocyte quality because of lipid accumulation and metabolic and oxidative stress 67 . In the present study, oocyte aerobic and anaerobic metabolism were significantly higher in OB than in NW mares, suggesting increased oocyte metabolic activity associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Oocyte development in a lipotoxic environment is thought to be one of the main negative effects of maternal obesity on fertility, as it promotes direct impairment of oocyte quality because of lipid accumulation and metabolic and oxidative stress 67 . In the present study, oocyte aerobic and anaerobic metabolism were significantly higher in OB than in NW mares, suggesting increased oocyte metabolic activity associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, controlling chronic low-grade inflammation and fibrosis in the ovary would represent a novel therapeutic strategy to improve the follicular microenvironment. Animal models have indicated that antioxidants ( 27 , 51 ), insulin-sensitizing drugs ( 125 ), anti-aging drugs (senolytics) ( 126 ), immune checkpoint inhibitors ( 127 ), and antifibrosis drugs ( 125 ) may help minimize follicular depletion and oocyte quality decline. However, further studies are required to determine whether these drugs overcome ovarian dysfunction in PCOS, endometriosis, and aging.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high ROS levels and low antioxidant capacity in follicular fluids were associated with poor pregnancy outcomes in human-assisted reproductive technology (ART) ( 49 , 50 ). Maternal conditions, including polycystic ovary syndrome (PCOS), endometriosis, and aging, may compromise the ovarian microenvironment ( 47 , 48 , 51 ). Therefore, the following sections discuss whether and how chronic low-grade inflammation negatively impacts ovarian function in PCOS, endometriosis, and aging.…”
Section: Pro-inflammatory Cytokines and Follicular Developmentmentioning
confidence: 99%
“…gestational diabetes and miscarriage) 2 , 3 . The detrimental effects of maternal obesity are evident at the level of the oocyte and early embryo 4 . This was confirmed in a study where pregnancy rates were restored in obese women when donor oocytes from healthy mothers were used 5 .…”
Section: Introductionmentioning
confidence: 99%